Gait Analysis Using the Physics Toolbox App (2022)
Sensors in new smartphones can be an excellent tool to measure different physical quantities and these can be useful to develop real experiments with application in human health. Therefore, in this research work, the design and construction of a gait analyser was carried out using the toolbox physics app for data acquisition and MATLAB was used for its analysis. This system analyses the behaviour of walking in people and its purpose is to diagnose any health problem caused by the human being's way of walking. For this, the g-force meter was used in x, y, and z components. This application uses inputs from the device's sensors to save and export the data in comma-separated values (CSV) format through a.csv extension. The results are very interesting because they can be used in medical diagnoses such as reduced gait speed and loss of regularity, symmetry, or synchronization of body movements. Since many organs are involved in gait, there are several types of gait disturbances that cause gait to be abnormal.With this system, it is possible to identify the hemiplegic gait, festinating gait, paraparhetic gait, waddling gait, among others. This analysis was carried out using the Pearson, Spearman, and Kendall correlation coef cients, which indicate the possible diagnoses in the patients.